RME Based Audiobook Development for Class IV Elementary School Students - Sari, Arissona Dia Indah; Herman, Tatang; Sopandi, Wahyu; Jupri, Al (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Learning mathematics at the Elementary School (SD) level is an important basis in building a good understanding of mathematical concepts in students. However, students often experience difficulties in understanding abstract and complex mathematical concepts. This can have an impact on reducing students' interest in learning mathematics. To overcome this problem, an audiobook based on RME (Realistic Mathematics Education) was developed which emphasizes the quality of sound recordings that are close to the experience of listening to voices directly, especially for mathematics materials at the elementary level. The research method used in this study is a research and development approach using the ADDIE model developed by Robert Maribe Branch. The ADDIE model is a development model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The results of the study show that audiobooks based on RME are valid and can be implemented in learning. Based on these results, the RME-based audiobook is ready to be implemented on a large scale and used as an effective alternative learning media in increasing conceptual understanding and interest in learning mathematics for fourth grade elementary school students in multiplication material.